DAMPAK RISIKO DEFAULT BANK TERHADAP RISIKO SISTEMIK PERBANKAN DAN RISIKO SISTEMATIK BURSA SAHAM DI LIMA NEGARA ASEAN - Buddi Wibowo; Wilbert Ham (University of Merdeka Malang, 2016)
AbstractGlobal financial crisis in 2008 has driven special attention to systemic banking sector risk that cause byindividual bank default. Though, banking crisis significantly affect economic growth and national macroeco-nomic condition. Individual bank default non only affect banking industry but also has serious injured theeconomy. Bank default risk not only affect systemic risk but also systematic risk.ASEAN financial integrationplan raise a need to understand characteristics of ASEAN banking industry. Close relationship and intercon-nection between ASEAN economies will make individual bank default a serious issue that its effect will spreadto all ASEAN economy. This research aimed to investigate the effect of bank default risk on systemic andsystematic risk in 5 ASEAN countries. We find that bank default risk significantlyraised systemic risk, esspeciallyin country with high concentration in its banking industry structure. Big banks tend to more serious effect onsystemic risk. Systematic risk tend to be affected by macroeconomy condition, rather than default risk ofindividual bank.